Regional Integration Dynamics in Central America: A perspective about the integration approach in the Anuario de Estudios Centroamericanos - Elizondo Borbón, Mariam Emilce (2024)
This text deals with regional integration in Central America. Its main objective is to evaluate the different approaches present on this subject in the Anuario de Estudios Centroamericanos (AECA). For this, the bibliography collected and studied during the Scientific Initiation project entitled: “Los proyectos de integración en las revistas de relaciones internacionales del continente americano (siglos XX y XXI)” was used; the investigation title is: “El Pensamiento Integracionista en el Anuario de Estudios Centroamericanos”. Firstly, a section was created with articles related to the subject until 2022, which resulted in a total of 43. Secondly, these texts were summarized and used as sources to group the information in order to carry out a historical follow-up of Central American integration. The research shows that there are insufficient articles on the subject in the AECA. Therefore, this situation must be analyzed from the point of view of scarcity, resulting in aspects such as: integration and peace, hegemonic integration, disintegrations, and migration. It is concluded that the weight of economic interests linked to the United States, the hegemonic power in the region, have reduced the relevance of the political and social aspects of cooperation that would benefit more people.